Gen-Z Local Wisdom Campaign Agenda in the Framework of Counter Hegemony, Digital Hegemony, Cultural Hegemony - Halifa Haqqi; Hasna Wijayati (Asian Journal of Community Services, 2023)
Gen Z is currently facing challenges from foreign hegemony that comes with digital technology. The research analyses Gen-Z local wisdom campaign agenda in framework of counter-hegemony, digital-hegemony, and cultural-hegemony. This study uses a method based on research-based development, involving 100 Gen-Z participants with a series of discussion agendas and a local wisdom campaign on their social media. Result show that local wisdom content can be a solution for educating young people to have positive activities such as getting to know local values, increasing nationalism, and counteracting negative impacts of foreign cultural hegemony. It concluded that local wisdom can be a counter to hegemony that takes place in the new era of digital hegemony, as form of cultural hegemony.